Land Acquisition for Public Interest Reviewed from the Principle of Social Function and the Principle of Justice at TPST Batargebang - Melnia, Nur Fitri (Universitas Islam Sultan Agung, 2025)
Land acquisition for public interest in Indonesia has limited land so the author will examine the government's considerations in determining areas for land acquisition reviewed from the principle of social function and examine the implementation of land acquisition for public interest against land rights reviewed from the principle of justice with the study area at TPST Batargebang. The writing is compiled using a normative legal research method that refers to legal norms contained in laws and regulations. The data processing method used is a qualitative method. Land acquisition for public interest at TPST Batargebang has implemented the principle of social function and the principle of justice by collaborating between the DKI Jakarta City Government and the Bekasi City Government.